Erzählte Rahmen: Realismus als Problem - Öhlschläger, Claudia (Rahmenbrüche, Rahmenwechsel)

Amor sacro e profano: Modelle und Modellierungen himmlischer und irdischer Liebe in Literatur und Malerei der italienischen Renaissance - Steigerwald, Jörn (‚Amor sacro e profano': Modelle und Modellierungen der Liebe in Literatur und Malerei der italienischen Renaissance)

Amor cortigiano. Die Modellierung höfischer Liebe im rinascimentalen Epos (am Beispiel von Ariostos „Orlando furioso“) - Steigerwald, Jörn (‚Amor sacro e profano’: Modelle und Modellierungen der Liebe in Literatur und Malerei der italienischen Renaissance)

Humorism: Literary Insights in Modern Times, According to Luigi Pirandello („L’Umorismo“, „Uno, nessuno e centomila“)2003 - Steigerwald, Jörn (Aisthesis und Noesis. Zwei Erkenntnis-Formen vom 18. Jahrhundert bis zur Gegenwart)

Erschriebene Bilder: Giovanni Boccaccios „Amorosa visione“ - Steigerwald, Jörn (Poiesis. Praktiken der Kreativität in den Künsten der Frühen Neuzeit)

De la querelle entre l'Arioste et le Tasse à la dispute entre l'ésthétique de l'Arioste et du Tasse. In: La dispute entre l'Arioste et le Tasse : Les appropriations de deux esthétiques antagonistes au XVIIe siècle en France - Steigerwald, Jörn; Roussillon, Marine (Papers on French Seventeenth Century Literatur XL, 79)

Himmlische Klänge: Die Paradiso-Cantica in Dantes „Divina Commedia“ - Steigerwald, Jörn; Ackermann , Christiane; Bleumer, Hartmut (LILI 171 (2013), Gestimmte Texte)

Äffische Nachahmung: Pietro Aretinos „Sei giornate“ - Steigerwald, Jörn (Wolfenbütteler Renaissance- Mitteilungen 34/1, 2012/2013)

De la comédie érudite à la comédie de salon: Les appropriations de l'Arioste par Molière („L'école des maris“, „L'école des femmes“, „La critique de l'école des femmes“). In: La dispute entre l'Arioste et le Tasse : Les appropriations de deux esthétiques antagonistes au XVIIe siècle en France - Steigerwald, Jörn; Roussillon, Marine (Papers on French Seventeenth Century Literature Literatur XL, 79)

La querelle des „Suppositi“ de l’Arioste - Steigerwald, Jörn (Littératures classiques 81, 2013, Le temps des Querelles, sous la direction de Jeanne-Marie Hostiou / Alain Viala)

Selbstbeurteilung. Fördermagazin Sekundarstufe Deutsch. Heft 4/2013

„Ich kann mich doch nicht selbst beurteilen…“ – Wege zur Selbstbeurteilung im Deutschunterricht. Basisbeitrag - Rezat, Sara (Fördermagazin Sekundarstufe 4/2013)

„Dann heiße ich doch lieber Pflaume!“. Mehrsprachige Literatur im Sprachförderunterricht - Zierau, Cornelia; Kofer, Martina (Chancen der Vielfalt nutzen lernen. Modellprojekt. (= http://www.kommunale-integrationszentren-nrw.de/sites/default/files/public/system/downloads/chancen_der_vielfalt_buch_internetversion_0.pdf))

„F. ist in einem Labyrint [sic!], er wird wohl kaum mehr herauskommen.“ – Mythologische und alttestamentarische Metaphern des Scheiterns in den Texten Franz Kafkas, Friedrich Dürrenmatts und Jorge Luis Borgesʼ - Famula, Marta (Kafka interkulturell. Forschungen der Deutschen Kafka-Gesellschaft)

Narrative Grenzgänger – Identitätskonstruktionen in zeitgenössischer Adoleszenz-Prosa. Annette Pehnts Insel 34 und Harald Grills gehen lernen - Famula, Marta (Corpora und Canones. Schlesien und andere Räume in Sprache, Literatur und Wissenschaft)

Erlebtes, Erkanntes und Fingiertes. Dürrenmatts ästhetisches Konzept der Epistemologie in seinem autobiographischen Projekt Stoffe I-IX - Famula, Marta (Auto(r)fiktion. Literarische Verfahren der Selbstkonstruktion)

Tribo-Dynamical Analysis of Cylindrical Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (VDI Berichte 2199)

Temperaturberechnung im RWDR-Dichtkontakt - Magyar, Balázs; Frölich, D; Sauer, B

Contact Modeling of Rough Surfaces - Magyar, Balázs; Sauer, B

Marte Meo als Supervisionsmethode: Eine Untersuchung über die Erfahrungen von Mitarbeitern und Mitarbeiterinnen einer Kindertagesstätte - Wächter, I.; Laubenstein, Désirée (In: Zeitschrift für Heilpädagogik, 64. Jahrgang, Nr. 4,)

Exploring reasons and consequences of academic procrastination: An interview study - Grunschel, Carola; Patrzek, Justine; Fries, Stefan (European Journal of Psychology of Education)

Exploring different types of academic delayers: A latent profile analysis - Grunschel, Carola; Patrzek, Justine; Fries, Stefan (Learning and Individual Differences)

Procrastination - Klingsieck, Katrin B. (European Psychologist)
Procrastination is a well-known phenomenon that often entails negative outcomes with regard to performance and subjective well-being. In an attempt to understand the (alarming) character of procrastination, a large body of research on the causes, correlates, and consequences of procrastination has been accumulating over the last 40 years. The aim of this paper is to provide a systematic characterization of the trends in procrastination research and to suggest future directions for research and practice. The systematic characterization comprises a comparison of procrastination to functional forms of delay (referred to as strategic delay) and a presentation of the theoretical approaches to explaining procrastination. The future directions suggested pertain to the development of a differentiated understanding of procrastination and of integral interventions.

Why Students Procrastinate: A Qualitative Approach - Klingsieck, Katrin B.; Grund, Axel; Schmid, Sebastian; Fries, Stefan (Journal of College Student Development)

Procrastination in Different Life-Domains: Is Procrastination Domain Specific? - Klingsieck, Katrin B. (Current Psychology)

Employability und Prokrastination aus einer hochschuldidaktischen Perspektive - Gerholz, Karl-Heinz; Klingsieck, Katrin B. (Das Hochschulwesen)

Kleine Wörter

Kleine Wörter - große Wirkung. Text schreiben mit "und", "trotzdem" und "weil" - Topalovic, Elvira; Tophinke, Doris; Uhl, Benjamin (Praxis Deutsch)

Kleine Wörter (Basisartikel) - Tophinke, Doris (Praxis Deutsch)

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

The light and dark side of TARP - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Banking and Finance)
Employing four event dates of the U.S. “Troubled Asset Relief Program” (TARP) this paper empirically investigates the impact of the first announcement of TARP (September 19, 2008), the announcement of revised TARP (October 14, 2008), respective capital infusions under TARP-CPP and capital repayments on changes in shareholder value and risk exposure of 125 supported U.S. banks as perceived by the capital market through share price reactions for an entire sample period from September 19, 2008 to June 16, 2010. Our analysis reveals a light and a dark side of TARP. While announcements as well as capital repayments may restore market confidence and financial stability, equity capital injections to banks are observed to be a severe impediment to an increase in bank shareholder value and financial soundness.
Keywords: Financial crisis; TARP; Market efficiency; Event study

Sprachliche Muster in der mittelniederdeutschen Rechtssprache. Zum Sachsenspiegel und zu Stadtrechtsaufzeichnungen des 13. bis 16. Jahrhunderts - Wallmeier, Nadine

Für eine veränderte Fachpraxis - Zur Kultur und Technik der Nahrungszubereitung und Mahlzeitengestaltung - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Haushalt in Bidlung und Forschung)

Der Wendenkreuzzug - Kamp, Hermann (Schwertmission. Gewalt und Christianisierung im Mittelalter)

Gewalt und Mission: Die Elb- und Ostseeslawen im Fadenkreuz des Reiches und der Sachsen vom 10. bis zum 12. Jahrhundert - Kamp, Hermann (Credo. Die Christianisierung Europas im Mittelalter)

Schwertmission. Gewalt und Christianisierung im Mittelalter

Korrekturen in sprachlichen Fächern - Hohwiller, Peter

Zur Handlungsvalidität von Tests zum professionellen Wissen von Lehrkräften - Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)

Vorratsbomben im Himmel. Über digitalen Terror, unsichtbare Opfer und die Rhetorik der Präzision - Weber, Jutta (Heinrich-Böll-Stiftung: High-Tech-Kriege: Frieden und Sicherheit in Zeiten von Drohnen, Kampfrobotern und digitaler Kriegsführung)

Automatisierte Verantwortungslosigkeit? Kampfdrohnen als Mittel der High-Tech-Kriegsführung - Weber, Jutta (FIfF Kommunikation 1/2013)

Efficient Power-Intent Validation Using "Loosely-Timed" Simulation Models: A Non-Invasive Approach - Mischkalla, Fabian; Müller, Wolfgang
Faced with increasing demands on energy efficiency, current electronic systems operate according to complex power management schemes including more and more fine-grained voltage frequency scaling and power shutdown scenarios. Consequently, validation of the power design intent should begin as early as possible at electronic system-level (ESL) together with first executable system specifications for integrity tests. However, today's system-level design methodologies usually focus on the abstraction of digital logic and time, so that typical low-power aspects cannot be considered so far. In this paper, we present a high-level modeling approach on top of the SystemC/TLM standard to simulate power distribution and voltage based implications in a "loosely-timed" functional execution context. The approach reuses legacy TLM models and prevents the need for detailed lock-step process synchronization in contrast to existing methods. A case study derived from an open source low-power design demonstrates the efficiency of our approach in terms of simulation performance and testability.
Keywords: Time-varying systems; Time-domain analysis; Synchronization; Context modeling; Clocks; Semantics; Standards

An Energy-Efficient Heuristic for Hard Real-Time System on Multi-Core Processors - He, Da; Müller, Wolfgang (Proceedings of the International Conference on Applied Computing (AC))
In the electronic system development, energy consumption is clearly becoming one of the most important design concerns. From the system level point of view, Dynamic Power Management (DPM) and Dynamic Voltage and Frequency Scaling (DVFS) are two mostly applied techniques to adjust the tradeoff between the performance and power dissipation at runtime. In this paper, we study the problem of combined application of both techniques with regard to hard real-time systems running on cluster-based multi-core processors. To optimize the processor energy consumption, a heuristic based on simulated annealing with efficient termination criterion is proposed. The experiment results show that the proposed algorithm outperforms the existing approaches in terms of the energy reduction.
Keywords: Dynamic Power Management; Dynamic Voltage and Frequency Scaling; Hard Real-Time; Multi-core Processor

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Does Mandatory IFRS Adoption Improve the Credit Relevance of Accounting Information? - Kosi, Urska; Florou, Annita; Pope, Peter F.

Positive Beispiele zu negativen Zahlen – Unterrichtsstudien zum~Mathematikunterricht. Verlängerungsantrag zum Forschungs- und Entwicklungsplan 2013–2015 - Althoff, Paula G.; Friedli, Reto; Hattermann, Mathias; Vom Hofe, Rudolf; Kullmann, Harry; Lukas, Janine; Viehmeister, Frauke (Laborschulforschung 2013. Anträge und Berichte zum forschungs- und Entwicklungsplan. Werkstattheft Nr. 48)

Learning by Doing – Improving Academic Skills - Temmen, Katrin; Walther, Thomas (International Journal of Engineering Pedagogy (iJEP))
Engineering faculties generally involve their students in the creation of numerous scientific works and publications. However, students are rarely trained in this area and could well benefit from targeted support: to this end, we propose a specific lecture that addresses the subtleties of scientific research and writing and allows the students to apply and mentally anchor their acquired knowledge while composing a basic scientific term paper.
Keywords: General Engineering; Education

'Learning by doing' Improving academic skills - Temmen, Katrin; Walther, T. (2013 IEEE Global Engineering Education Conference (EDUCON))

Auf die Studierenden hören: Einsatz von Schülerlaboren in der Lehramtsausbildung - Temmen, Katrin (Didaktik im Fokus)

Lehrerbildung praxisorientiert gestalten - Das Projekt InnoTrans Uni-BK - Gerholz, K.-H.; Bödeker, J.; Eberhardt, A.; Kerstingtombroke, D.; Langeleh, D.; Temmen, Katrin (Wirtschaft und Erziehung)

Identifying and Tackling Inequality: A Challenge for Social Work - Dahmen, Stephan; Beuret, Benoit; Bonvin, Jean-Michel (Schweizerische Zeitschrift für Soziale Arbeit/Revue suisse de travail social)